2022
DOI: 10.1002/macp.202200334
|View full text |Cite
|
Sign up to set email alerts
|

Poly(oxanorbornene)‐Based Polyzwitterions with Systematically Increasing Hydrophobicity: Synthesis, Physical Characterization, and Biological Properties

Abstract: Surfaces coated with polyzwitterions are known to resist protein adhesion and to be generally bio‐inert. In recent reports, several polyzwitterionic coatings with carboxylate groups and intrinsic antimicrobial activity due to the pH‐responsivity of that group are described, but the design rules to obtain such activity remain unclear. Therefore, in this work, a set of surface‐attached polyzwitterions with carboxylate groups and varying alkyl residues is studied. The gradually increasing hydrophobicity of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…While ethyl and butyl groups do neither affect the wettability nor the NSA of proteins, an increase of the alkyl chain length from hexyl to octyl increased the WCA and CBCA substantially and increased the NSA of fibrinogen (Fg). ( Paschke et al, 2022 ). Literature also reported that copolymers consisting of PC and BMA showed increasing resistance with increasing zwitterionic content with the highest resistance achieved by the highest zwitterionic content of 30%.…”
Section: Discussionmentioning
confidence: 99%
“…While ethyl and butyl groups do neither affect the wettability nor the NSA of proteins, an increase of the alkyl chain length from hexyl to octyl increased the WCA and CBCA substantially and increased the NSA of fibrinogen (Fg). ( Paschke et al, 2022 ). Literature also reported that copolymers consisting of PC and BMA showed increasing resistance with increasing zwitterionic content with the highest resistance achieved by the highest zwitterionic content of 30%.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Lienkamp and coworkers have also reported poly(oxanorbornene)-based polyzwitterions (Fig. 17) whereby the hydrophilicity/hydrophobicity balance of the materials could be engineered at will, 95 thus allowing for fine control over their resulting properties and applications. Specifically, the polymers with short alkyl residues (e.g., Me) were more hydrophilic and antifouling than the analogs with longer alkyl chains, resisting adhesion to proteins and human cells easily but showing no antimicrobial activity.…”
Section: Polyzwitterionsmentioning
confidence: 99%
“…More recently, Lienkamp and coworkers have also reported poly(oxanorbornene)-based polyzwitterions (Fig. 17) whereby the hydrophilicity/hydrophobicity balance of the materials could be engineered at will, 95 thus allowing for fine control over their resulting properties and applications. Specifically, the polymers with short alkyl residues ( e.g.…”
Section: Antifouling Stealth Polymers In Nanomedicinementioning
confidence: 99%
“…[17,18] Nevertheless, several recent reports note the susceptibility of PEG-based polymers to oxidation and the induction of immunogenic responses. [19][20][21] On top of a certain hydrophilicity, [22][23][24][25][26] a neutral net charge and hydrogen bond acceptors at the interface were identified as key design rules for inert coatings. [17] Zwitterionic materials [27][28][29] fulfill these requirements and are capable to form strong bonds with surrounding water molecules by electrostatically induced hydration.…”
Section: Introductionmentioning
confidence: 99%
“…On top of a certain hydrophilicity, [ 22–26 ] a neutral net charge and hydrogen bond acceptors at the interface were identified as key design rules for inert coatings. [ 17 ] Zwitterionic materials [ 27–29 ] fulfill these requirements and are capable to form strong bonds with surrounding water molecules by electrostatically induced hydration.…”
Section: Introductionmentioning
confidence: 99%